2021
DOI: 10.1097/hjh.0000000000002953
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium and cardiovascular morbidity/mortality: a brief commentary on the ‘J-shape hypothesis’

Abstract: The last decade, a growing number of evidence support Jshape or inverse -instead of positive linear -associations between dietary sodium intake and cardiovascular morbidity/mortality. A careful evaluation of these studies leads to the following observations: less accurate methods for dietary sodium assessment are usually used; most studies included high-risk participants, enhancing the possibility of a 'reverse causality' phenomenon. However, these limitations do not explain all the findings. Few carefully des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 99 publications
(214 reference statements)
0
2
0
Order By: Relevance
“…Some studies suggest a “J-shaped” relationship between salt intake and the incidence of cardiovascular events. 31 However, the presence of a comparable relationship between salt intake and aging necessitates further evidence for validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest a “J-shaped” relationship between salt intake and the incidence of cardiovascular events. 31 However, the presence of a comparable relationship between salt intake and aging necessitates further evidence for validation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest a "J-shaped" relationship between salt intake and the incidence of cardiovascular events. 31 However, the presence of a comparable relationship between salt intake and aging necessitates further evidence for validation. We conducted analyses in different subgroups to explore the relationship between dietary quality and accelerated aging, assessing potential variations among populations with distinct characteristics.…”
Section: Papermentioning
confidence: 99%
“…Studies have shown that there is a J-shaped association of dietary salt intake with mortality and cardiovascular events [ 33 , 34 ]. In this study, we found that the new-incident CSVD was positively correlated with salt intake and the J-shape curve was less obvious.…”
Section: Discussionmentioning
confidence: 99%
“… 5 An acute decrease in serum osmolality was also a risk factor for potentially severe postoperative neurologic complications following kidney transplantation. 6 It has been proven that the components of the formula, namely sodium, 7 blood urea nitrogen, 8 serum glucose, 9 and other parameters interacting with osmolality such as serum albumin 10 and renal function, 11 affect all-cause and cause-specific mortality in general population, while few studies have elucidated about the prognostic meaning of osmolality itself in all-cause and cause-specific mortality in diabetic population.…”
Section: Introductionmentioning
confidence: 99%